2001
DOI: 10.1017/s0031182001008411
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between the gelatin-binding domain of fibronectin and the attachment ofPasteuria penetransendospores to nematode cuticle

Abstract: Pasteuria penetrans is a Gram-positive endospore-producing bacterium that is a parasite of root-knot nematodes. Attachment of endospores to the cuticle of the nematode is the first stage in the infection process. Western blot analysis with monoclonal and polyclonal antibodies that recognize the 30 kDa heparin-binding domain (HBD) and the 45 kDa gelatin-binding domain (GBD) fragments of human fibronectin (Fn) revealed a series of polypeptides of approximately 40, 45 and 55 kDa present in crude cuticle extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Other studies add mechanistic support to the hypothesis that infection success is determined before the parasite reaches the host's hemocoel: Duneau et al (2011) observed attachment of P. ramosa spores on the esophagus of a susceptible D. magna genotype, but a distinct lack of attachment in a resistant genotype. A related parasite, P. penetrans , infects its nematode hosts by attaching to the heparin‐binding domain of the host cuticle (Sayre and Starr 1985; Mohan et al 2001; Schmidt et al 2008). To persist in the host population, such receptors would have evolved for another important purpose, perhaps for the recognition of nutrients, symbionts or commensal bacteria, and certain parasite strains may have taken advantage of these receptors by expressing chemical features that imitate food or commensal bacteria—“wolves in sheep's clothing.” The ability of a host to recognize and eliminate a parasite may depend on a lock‐and‐key mechanism where each receptor must effectively bind to a molecular feature on the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies add mechanistic support to the hypothesis that infection success is determined before the parasite reaches the host's hemocoel: Duneau et al (2011) observed attachment of P. ramosa spores on the esophagus of a susceptible D. magna genotype, but a distinct lack of attachment in a resistant genotype. A related parasite, P. penetrans , infects its nematode hosts by attaching to the heparin‐binding domain of the host cuticle (Sayre and Starr 1985; Mohan et al 2001; Schmidt et al 2008). To persist in the host population, such receptors would have evolved for another important purpose, perhaps for the recognition of nutrients, symbionts or commensal bacteria, and certain parasite strains may have taken advantage of these receptors by expressing chemical features that imitate food or commensal bacteria—“wolves in sheep's clothing.” The ability of a host to recognize and eliminate a parasite may depend on a lock‐and‐key mechanism where each receptor must effectively bind to a molecular feature on the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…The P. ramosa infection process may be similar to that seen in Pasteuria penetrans , a sterilizing parasite that initiates infections by attaching to the heparin-binding domain and gelatine-binding domain proteins on the cuticle of Meloidogyne nematodes (Sayre & Starr 1985; Mohan et al . 2001; Schmidt et al .…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the cuticle receptor(s) for Pasteuria adhesion is ambiguous. Persidis et al, (1991) showed that collagen may be responsible for the recognition process, because cuticle components involved in attachment are sensitive to trypsin and endoglycosidase F, and because gelatin (denatured collagen) itself can inhibit spore attachment (Persidis et al, 1991;Mohan et al, 2001). However, the incubation of second-stage juveniles in the presence of (Mankau et al, 1976;Sayre & Wergin, 1977;Morton et al, 2004;Huang et al, 2005).…”
Section: Mechanisms Of Infectionmentioning
confidence: 99%